2018
DOI: 10.1101/501437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relation between Alpha/Beta Oscillations and the Encoding of Sentence induced Contextual Information

Abstract: Within the sensory domain, alpha/beta oscillations have been frequently linked to the prediction of upcoming sensory input. Here, we investigated whether oscillations at these frequency bands serve as a neural marker in the context of linguistic input prediction as well.Specifically, we hypothesized that if alpha/beta oscillations do index language prediction, their power should modulate during sentence processing, indicating stronger engagement of underlying neuronal populations involved in the linguistic pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 52 publications
4
23
1
Order By: Relevance
“…Applied to language processing, interplay between top-down predictions, instantiated by beta activity, and bottom-up error signaling might play a role in maintaining and updating a representation of discourse context important for flexible online comprehension (Lewis et al, 2016;Meyer et al, 2018). Within this framework, beta band suppression may have occurred selectively as people updated relevant information about trial content or pseudoword meaning, whereas in Meaning (-) trials the semantic incoherence across sentences prevented stable contextual representations from being formed to begin with-which is likely the reason we did not find evidence for similar suppression effects in response to pseudowords themselves Additionally, recent work using MEG directly tested the relationship between power suppression effects during sentence encoding and word predictability and found that neither alpha nor beta band activity held a monotonic relationship with the level of contextual constraint provided by the sentence context (Terporten et al, 2019). This indicates these mechanisms are not merely an index of upcoming word predictability and may instead relate more closely to information updating during sentence processing.…”
Section: Alpha and Beta Suppression Within Meaningful Contextscontrasting
confidence: 61%
“…Applied to language processing, interplay between top-down predictions, instantiated by beta activity, and bottom-up error signaling might play a role in maintaining and updating a representation of discourse context important for flexible online comprehension (Lewis et al, 2016;Meyer et al, 2018). Within this framework, beta band suppression may have occurred selectively as people updated relevant information about trial content or pseudoword meaning, whereas in Meaning (-) trials the semantic incoherence across sentences prevented stable contextual representations from being formed to begin with-which is likely the reason we did not find evidence for similar suppression effects in response to pseudowords themselves Additionally, recent work using MEG directly tested the relationship between power suppression effects during sentence encoding and word predictability and found that neither alpha nor beta band activity held a monotonic relationship with the level of contextual constraint provided by the sentence context (Terporten et al, 2019). This indicates these mechanisms are not merely an index of upcoming word predictability and may instead relate more closely to information updating during sentence processing.…”
Section: Alpha and Beta Suppression Within Meaningful Contextscontrasting
confidence: 61%
“…Beta oscillations in pars triangularis and ATL may be preparing a syntactic slot to be filled by predicted upcoming nominal content, or they could be initiating top-down local coordination of subsequent composition-indexing BGA in pSTS-TOJ. Following other recent findings (Terporten et al, 2019), it is possible that these beta dynamics do not pertain to lexico-semantic prediction specifically, but rather anticipatory stages pertaining to phrasal initiation. Our findings are also potentially in line with the notion that beta oscillations can index the construction and maintenance of sentence-level meaning (scaling up from minimal phrases) (Lewis et al, 2016), and also the claims that beta can index aspects of syntactic anticipation and phrasal category generation (Benítez-Burraco and Murphy, 2019;Murphy, 2020), since all phrases were predictably nominal phrases.…”
Section: Anticipatory Responsementioning
confidence: 52%
“…We next contrasted Adjective-Noun and Pseudoword-Noun conditions at the onset of second word presentation, with only the former condition licensing any phrasal anticipation. Given that both traditional alpha (8-12 Hz) and beta (12-30 Hz) bands have been regularly implicated in linguistic prediction and anticipatory composition (Lewis et al, 2016;Segaert et al, 2018;Hardy et al, 2021), with previous research in this domain (Gisladottir et al, 2018;Terporten et al, 2019) and neighboring domains (Piai et al, 2020) collapsing these bands, we analyzed activity across the 8-30 Hz range. During the anticipatory window for phrase formation (from -200ms to 0 ms prior to the second word onset), low frequency power (8-30 Hz) exhibited a significant conditional difference (Fig.…”
Section: Compositional Anticipationmentioning
confidence: 99%
“…Delta (1-4Hz) and low-beta (14-21Hz) oscillations, which are also frequently observed in relation with speech processing, have a more endogenous origin. While delta is argued to play a role in syntactic parsing (Ding et al, 2015(Ding et al, , 2017, beta (15-30Hz) oscillations are associated with comprehension and top-down effects, without being related to specific linguistic units or language operations (Lewis and Bastiaansen, 2015;Pefkou et al, 2017;Keitel, Gross and Kayser, 2018;Terporten et al, 2018;Abbasi and Gross, 2020).…”
Section: Introductionmentioning
confidence: 99%